Analisis Keluhan Konsumen Pembelian Produk Honda Vario di PT. Niaga Utama Sejahtera - Ilham Ramadian; Hikmal J; Syamsul Hidayat (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research aims to determine consumer complaints when purchasing Honda Vario products at PT. Utama Niaga Sejahtera. The research method uses qualitative methods by providing several statements to the respondents. The population of this research is several people in Serang City who own Honda Vario vehicles. The sampling technique is using random sampling or random samples and distributing questionnaires, namely by distributing them online. There are 57 respondents who are willing to fill out the questionnaire so that the sample used is 57 samples. The results of the research show that the response regarding complaints about the Honda Vario motorbike among consumers is still responded well, where the complaints felt about the Honda Vario motorbike product are still at a reasonable stage so that these shortcomings have been covered by the specifications of the advantages of the Honda Vario motorbike which even other vehicle units do not have advantages.